The art, science, and technology of pharmaceutical compounding - Allen, Jr., Loyd V. (Washington, D.C : American Pharmacists Association, 2012)
The practice of pharmacy compounding continues to grow. Factors contributing to the expanding role of the compounding pharmacists in health care include drugs shortages, the discontinuation of drug products, the lact of pediatric formulations, hospitals outsourcing of compounding through the contracts with independent and specialty pharmacies, veterinary compounding, the need for altenative drug delivery and for dosage adjustments, and the use of short-dates (unstable) drugs.
Guidelines for compounding practices -- Compounding ingredient considerations -- Facilities, equipment, and supplies -- Records and record keeping -- Stability of compounded preparations -- Pharmaceutical compounding calculations -- Quality control -- Flavors, sweeteners, and colors -- Preservation, sterilization, and depyrogenation -- Powders and granules -- Capsules -- Tablets -- Lozenges/Troches -- Suppositories and inserts -- Sticks -- Solutions -- Suspensions -- Emulsions -- Ointments, creams, and pastes -- Gels -- Ophthalmic, otic and nasal preparations -- Inhalation preparations -- Parenteral preparations -- Biotechnology, nanotechnology and pharmacogenomics -- Special populations and preparations -- Veterinary pharmaceuticals -- Compounding for clinical studies -- Cosmetics for special populations and for use as vehicles -- Compounding with hazardous drugs -- Compounding for terrorist attacks and natural disasters
Includes bibliographical references and index.
Keywords: DRUG COMPOUNDING